Analisis Nilai-Nilai Pancasila dalam Meningkatkan Gotong Royong Masyarakat - Acep Acep (Universitas Indraprasta PGRI, 2026)
This study aims to examine how Pancasila values play a role in reviving the spirit of mutual cooperation among the people of Kp. Stangkle Kelurahan Kemirimuka, Kecamatan Beji Depok. The background of this study departs from the phenomenon of a diminishing sense of togetherness in society influenced by the development ofmodernization and the increasing tendency towards individualistic lifestyles. The approach used is descriptive qualitative with data collection methods through interviews, observations, and documentation of village officials and the local community. This research was conducted on 10, october 10, 2025, with a frequency of 6 meetings, each lasting 3-4 hours in 12 effective days of research.The results of the study indicate that Pancasila values are still implemented in real life, especially in mutual cooperation activities such as community service, construction of public facilities, and socio religious activities. The value of divinity is reflected through an attitude of tolerance between religious communities, the value of humanity through social concern, the value of unity through community cohesion, the value of democracy through deliberation in decision-making, and the value of justice through an equitable distribution of tasks. The conclusion of this study shows that the application of Pancasila values has an important role in strengthening social solidarity and maintaining harmony among residents of Kp. Stangkle Kelurahan Kemirimuka, Kecamatan Beji Depok.